Organic chemistry for dummies - Winter, Arthur (Wiley Publishing, 2005)
Organic chemistry is rated among the most difficult courses that students take and is frequently the cause of washout among pre-med, medical, and nursing students. This book is an easy-to-understand and fun reference to this challenging subject. It explains the principles of organic chemistry in simple terms and includes worked-out problems to help readers get up to speed on the basics.